DEUS Enthesitis Index (DEI): a new tool integrating ultrasound and clinical examination for enthesitis assessment in spondyloarthritis - Emilio Filippucci; Andrea Di Matteo; Stefano Di Donato (RMD Open)
Objectives (1) To develop a composite score, the DEUS (Defining Enthesitis on Ultrasound in Spondyloarthritis) Enthesitis Index (DEI), which integrates ultrasound and clinical examination findings for enthesitis assessment in patients with spondyloarthritis (SpA); (2) to examine the relationships between DEI and clinical features in this population, compared to the clinical examination of the entheses alone.Methods This was a cross-sectional, observational, multicentric study involving 20 rheumatology centres across 11 countries. Ultrasound and clinical examinations were performed bilaterally on the lower limb large entheses (ie, quadriceps tendon, proximal and distal patellar tendons, Achilles tendon and plantar fascia) in 413 patients with SpA, including 224 patients with axial SpA and 189 patients with psoriatic arthritis (PsA). A score of 1.0 for clinical enthesitis and 1.0 for ultrasound enthesitis was assigned for each of the 10 entheses evaluated. The total DEI score, which combines clinical and ultrasound findings, ranged from 0 to 20 per patient. Logistic and gamma regression models based on DEI were compared with those derived solely from clinical enthesitis assessment to evaluate their relative performance in explaining disease-related outcomes.Results Among patients with SpA, the median DEI was 1.0 (IQR 0.0–3.0). DEI showed significant associations with SpA disease activity and severity indices in regression analyses, except for the Disease Activity in Psoriatic Arthritis score in patients with PsA. Compared with the clinical examination alone of the same entheses, DEI models exhibited a significantly better fit with C-reactive protein levels and ultrasound-detected structural damage at the enthesis (ie, enthesophytes and bone erosions). By contrast, the clinical examination alone models showed a significantly stronger fit with SpA disease activity indices and patient-reported outcomes compared with the DEI.Conclusions DEI is a novel tool that integrates both ultrasound and clinical examination findings for enthesitis assessment, potentially ensuring a more reliable evaluation of this key domain in SpA.